Clinical autonomic dysfunction in narcolepsy type 1. Issue 12 (16th August 2019) - Barateau, Lucie; Chenini, Sofiene; Evangelista, Elisa; Jaussent, Isabelle; Lopez, Regis; Dauvilliers, Yves
Abstract: Study Objectives: (1) To compare the presence of autonomic symptoms using the validated SCOPA-AUT questionnaire in untreated patients with narcolepsy type 1 (NT1) to healthy controls, (2) to study the determinants of a high total SCOPA-AUT score in NT1, and (3) to evaluate the effect of drug intake on SCOPA-AUT results in NT1. Methods: The SCOPA-AUT questionnaire that evaluates gastrointestinal, urinary, cardiovascular, thermoregulatory, pupillomotor, and sexual dysfunction was completed by 92 consecutive drug-free adult NT1 patients (59 men, 39.1 ± 15.6 years old) and 109 healthy controls (63 men, 42.6 ± 18.2 years old). A subgroup of 59 NT1 patients completed the questionnaire a second time, under medication (delay between two evaluations: 1.28 ± 1.14 years). Results: Compared to controls, NT1 patients were more frequently obese, had more dyslipidemia, with no difference for age and gender. The SCOPA-AUT score of NT1 was higher than in controls in crude and adjusted models. Patients experienced more problems than controls in all subdomains. A higher score in NT1 was associated with older age, longer disease duration, altered quality of life and more depressive symptoms, but not with orexin levels and disease severity. Among patients evaluated twice, the SCOPA-AUT score total did not differ according to treatment status, neither did each subdomain. Conclusion: We captured a frequent and large spectrum of clinical autonomic dysfunction in NT1, with impairment in all SCOPA-AUT domains, without key impact of medication intake. This assessment may allow physicians to screen and treat various symptoms, often not spontaneously reported but associated with poor quality of life.